IS THE DEVIL IN THE DETAILS? Tension Between Minimalism and Comprehensiveness in the Shariah - Brown, Jonathan A. C. (Journal of religious ethics, 2011)
The comprehensiveness of Islamic law has been questioned seriously in the modern period by Muslim reformists like Rashīd Riḍā. Such reformists have used as evidence Qur'anic verses and Prophetic reports that seem to state clearly that the strictures of Islamic law are few and limited and that Muslims should not extend them to all areas of life. How could the Shariah have developed as a holistic and exhaustive body of law in light of such evidence? Looking back at earlier Muslim scholars from the ninth to the eighteenth centuries, however, we see that these Qur'anic verses and Prophetic edicts were never understood in this way. They were either diffused with various hermeneutic strategies or understood as applying to debates unrelated to the comprehensiveness or minimalism of the Shariah.